A small 'lick' will sink a great ship: fulminant septicaemia after dog saliva wound treatment in an asplenic patient. Issue 6 (19th April 2017) - Morandi, Evi M; Pauzenberger, Reinhard; Tasch, Christoph; Rieger, Ulrich M; Pierer, Gerhard; Djedovic, Gabriel
ABSTRACT: Capnocytophaga canimorsus is a bacterium transmitted through the saliva of dogs. An infection can cause severe sepsis with acral necrosis and is potentially fatal. Here, we report the case of a 41‐year‐old man who was infected through a wound that was licked by his dog. He went into septic shock with disseminated intravascular coagulation and subsequently lost both lower legs, his nose and all the fingers on both hands.